2008
DOI: 10.7589/0090-3558-44.1.99
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium Bovis in Wildlife in France

Abstract: ABSTRACT:In early 2001, tuberculosis-like lesions were detected in three hunter-killed red deer (Cervus elaphus) in the Brotonne Forest (Normandy, France), and Mycobacterium bovis was isolated. In subsequent hunting seasons, two surveys were conducted in the area. In the first survey 55.13, df51, P50.02). Wild boar (Sus scrofa) were heavily infected in both surveys. One roe deer (Capreolus capreolus) and one red fox (Vulpes vulpes) also tested positive in the second survey. Mycobacterium bovis was not isolated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
111
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(115 citation statements)
references
References 20 publications
3
111
0
1
Order By: Relevance
“…Deer infected with M. bovis were discovered in North America (22), in the United Kingdom (6,7), in the Republic of Ireland (28), in Spain (2), and in France (40). M. bovis has frequently been isolated in wild boar in Western Europe, especially in France, Spain, and Italy (26,32,40). Even when M. bovis is not yet isolated from wildlife, this risk must not be dismissed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deer infected with M. bovis were discovered in North America (22), in the United Kingdom (6,7), in the Republic of Ireland (28), in Spain (2), and in France (40). M. bovis has frequently been isolated in wild boar in Western Europe, especially in France, Spain, and Italy (26,32,40). Even when M. bovis is not yet isolated from wildlife, this risk must not be dismissed.…”
Section: Discussionmentioning
confidence: 99%
“…This is the case for badgers in the United Kingdom and in the Republic of Ireland (4,8,17) and for brush-tail possums in New Zealand (24). Deer infected with M. bovis were discovered in North America (22), in the United Kingdom (6,7), in the Republic of Ireland (28), in Spain (2), and in France (40). M. bovis has frequently been isolated in wild boar in Western Europe, especially in France, Spain, and Italy (26,32,40).…”
Section: Discussionmentioning
confidence: 99%
“…There is a clear indication that wild boar could be the source of bTB infection for domestic animals and humans, especially hunters and veterinarians. Zanella et al (2008) reported that an outbreak of tuberculosis in wildlife in France, especially in heavily infected wild boars, was due to the same strain of M. bovis isolated from other wildlife and domestic cattle.…”
Section: Bacteria In Wild Boars That Are Potentially Transmissible Tomentioning
confidence: 99%
“…There is strong evidence that bison are currently the only wildlife reservoir of M. bovis and B. abortus in northern Canada (Shury et al 2006;Wobeser 2009), making eradication of these two pathogens a realistic objective without compromising the ecological integrity of northern ecosystems. This is in contrast to other parts of the world where multiple species are potential reservoirs of B. abortus (Kriek 2006;Zanella et al 2008).…”
Section: Discussionmentioning
confidence: 57%